Tingkat Engagement terhadap Konten Confession pada Akun Instagram @noelalexxander - Mirta Riski Utami; Hudi Santoso; Leonard Dharmawan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the relationship between confession content on the Instagram account @noelalexxander and the level of follower engagement. Confession content is a post in the form of a confession or personal story sent anonymously by users and has the potential to increase digital interaction through likes, comments, and shares. This study uses a quantitative descriptive-correlational approach with a sample of 100 followers whose data were obtained through a questionnaire. The research instrument was tested for validity and reliability, and analyzed using descriptive tests, normality tests, Spearman correlation, and linear regression. The results show that confession content significantly affects follower engagement. The more relevant and emotional the uploaded content, the higher the audience engagement. This finding supports the uses and gratifications theory which states that audiences actively choose content that meets their psychological and social needs, and strengthens the evidence that personal and authentic content can build emotional closeness and more intense interactions on social media. This study provides practical implications for social media account managers to create authentic, relevant, and ethical content.